Multi-responsive polypeptide hydrogels derived from N-carboxyanhydride terpolymerizations for delivery of nonsteroidal anti-inflammatory drugs. Issue 24 (2nd June 2017) - Fan, Jingwei; Li, Richen; Wang, Hai; He, Xun; Nguyen, Tan P.; Letteri, Rachel A.; Zou, Jiong; Wooley, Karen L.
Abstract : Multi-responsive polypeptide-based hydrogels exhibited thermo-, mechano-, and enzyme-responsive properties, enabling performance as a delivery system for encapsulation and release of naproxen. Abstract : A polypeptide-based hydrogel system, when prepared from a diblock polymer with a ternary copolypeptide as one block, exhibited thermo-, mechano- and enzyme-responsive properties, which enabled the encapsulation of naproxen (Npx) during the sol–gel transition and its release in the gel state. Statistical terpolymerizations ofl -alanine (Ala), glycine (Gly) andl -isoleucine (Ile) NCAs at a 1 : 1 : 1 feed ratio initiated by monomethoxy monoamino-terminated poly(ethylene glycol) afforded a series of methoxy poly(ethylene glycol)- block -poly(l -alanine- co -glycine- co -l -isoleucine) (mPEG- b -P(A-G-I)) block polymers. β-Sheets were the dominant secondary structures within the polypeptide segments, which facilitated a heat-induced sol-to-gel transition, resulting from the supramolecular assembly of β-sheets into nanofibrils. Deconstruction of the three-dimensional networks by mechanical force (sonication) triggered the reverse gel-to-sol transition. Certain enzymes could accelerate the breakdown of the hydrogel, as determined by in vitro gel weight loss profiles. The hydrogels were able to encapsulate and release Npx over 6 days, demonstrating the potential application of these polypeptide hydrogels as an injectable local delivery system for small molecule drugs.